Maritime Content in Indonesian History Education: The Development and Alternative Solution - Wasino Wasino (Journal of Maritime Studies and National Integration, 2017)
For a long time ago, Indonesia was identified as maritime country. The collective memory remembered from several islands in Indonesia shows that Indonesia is a large maritime space. The original name of the country was Nusantara, (called archipelago in English). From historical data in some location, there are some evidences about the glorious of the maritime kingdom in the continent. However, maritime perspective is not to be ‘important issue” in the mind of Indonesian people nowadays. History education makes an important rule at the moment. Indonesian independence needs history education based on political perspective, especially to enhance nationalism. The orientation is continued until the New Order, and it is especially focused on the rule of Indonesia military. Reformation since 1998 should make democratization in Indonesian history teaching, but the reality, the tradition of writer in history education, was still stagnant. The content of maritime history in Indonesian History Education still become a big problem. This paper aims to analyze the development of the maritime content in Indonesian History education at school and to give the new alternative in teaching history based on maritime content. The alternative curriculum based on local competitiveness in maritime history related with regional and global region, is the best solution for it.